Postoperative Complications After Prophylactic Thyroidectomy for Very Young Patients With Multiple Endocrine Neoplasia Type 2. Issue 29 (July 2015) - Kluijfhout, Wouter P.; van Beek, Dirk-Jan; Verrijn Stuart, Annemarie A.; Lodewijk, Lutske; Valk, Gerlof D.; van der Zee, David C.; Vriens, Menno R.; Borel Rinkes, Inne H.M.; Enrico, Brignardello.
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to investigate whether younger age at surgery is associated with the increased incidence of postoperative complications after prophylactic thyroidectomy in pediatric patients with multiple endocrine neoplasia (MEN) 2. The shift toward earlier thyroidectomy has resulted in significantly less medullary thyroid carcinoma (MTC)-related morbidity and mortality. However, very young pediatric patients might have a higher morbidity rate compared with older patients. Hardly any literature exists on complications in the very young. A retrospective single-center analysis was performed on the outcomes of MEN2 patients undergoing a prophylactic total thyroidectomy at the age of 17 or younger. Forty-one MEN2A and 3 MEN2B patients with thyroidectomy after January 1993 and at least 6 months of follow-up were included, subdivided in 9 patients younger than 3 years, 15 patients 3 to 6 years, and 20 patients older than 6 years. Postoperative hypocalcemia and other complications were registered. Twelve (27%) patients developed transient hypocalcemia and 9 (20%) patients suffered from permanent hypocalcemia, with a nonsignificant trend toward higher incidence with decreasing age. Three (7%) patients had other complications, of whom 2 were younger than 3 years. For patients younger than 3 years, the average length of stay (LOS) was 6.7 days, versus 1.7 and 3.5 days, respectively, for the older patient groups (P < 0.05). Patients with complications had a longer LOS compared with patients without (5.0 vs 2.0, P < 0.01). None of the patients had clinical signs of recurrent MTC after a mean follow-up of 10.5 years. Prophylactic thyroidectomy in very young children is associated with a higher rate of complications, causing a significant increased LOS. Irrespective age of surgery, MTC did not recur in any patient. In planning optimal timing of surgery, clinicians should take the risk of complications into account. We advise not to perform total thyroidectomy before the age of 3 for patients defined high risk by the American Thyroid Association guideline.